Introduction to financial management - Smart, Scott B.; Graham, John R. 1961- (South-Western, Cengage Learning, 2012)
Emphasizes the roles of financial managers and CFOs and shows how financial management actually works in real companies. This title offers timely examples and new material on the financial crisis, innovative online learning tools, and enables you to keep students of varying degrees of ability both motivated and involved.